Effect of Insecurity on Educational Delivery in Public Schools - Wanjara, Amos Otieno; Ogembo, Paul Okeyo (ETDC: Indonesian Journal of Research and Educational Review, 2024)
Insecurity is a concern in the North Eastern (N.E.) and North Rift (N.R.) parts of Kenya. The study aimed to assess the effects of insecurity on educational delivery in public schools in these regions. The objectives were to establish the causes and nature of insecurity, the effects of insecurity on attendance, and the way forward to insecurity on educational delivery in these regions. The study utilized a meta-analytic approach, according to Ferrer (1998). Results indicate that livestock rustling and terrorist attacks from Al-Shabaab are major causes of insecurity. The recent mass exodus of teachers from the Northeast region has challenged education delivery. Insecurity has led to low student attendance and school closures. The findings have implications for national governments, such as the Ministry of Interior and county governments, who must devise sustainable and robust security logistics to foster peaceful coexistence. This would not only enhance the delivery of education effectively but also streamline other transactions that are common in every society.